Vertex Hyper-Zagreb Index of Graphs - Pattabiraman, K.; Seenivasan, M. (International Journal of Engineering and Technology, 2018)
In this paper, we obtain the vertex hyper-Zagreb index for some composite graphs. Using the results obtained here, the vertex hyper-Zagreb index for some important classes of graphs are obtained.Â Â